FGFR2 is an oncogenic driver critical for successful human gammaherpesvirus latent infection and oncogenesis - Nian Ma; Dipayan Bose; Jakob Svoboda; Elise A. Chong; Stephen J. Schuster; Erle S. Robertson (Proceedings of the National Academy of Sciences, 2026)
Epstein–Barr virus (EBV) and Kaposi’s sarcoma–associated herpesvirus (KSHV) drive multiple aggressive lymphomas, yet effective targeted therapies for these virus-associated malignancies remain limited. Using an unbiased kinome-wide screen combined with analysis of virus-positive patient tumors, we identified fibroblast growth factor receptor 2 (FGFR2) as a selectively activated host kinase in EBV- and KSHV-associated lymphomas. Importantly, FGFR2 is required for efficient establishment of EBV latent infection, and its knockdown markedly impairs the formation of viral latency programs. Viral latency proteins EBV nuclear antigen 2 (EBNA2) and latency-associated nuclear antigen (LANA) recruit STAT3 and RBP-Jκ to the FGFR2 promoter to drive its transcription, enabling efficient establishment of EBV latency and activation of downstream STAT3/AKT signaling. This feed-forward signaling circuit suppresses apoptosis, promotes S-phase progression, and sustains proliferation of infected lymphoma cells. Targeting FGFR2 genetically or pharmacologically using clinically relevant inhibitors markedly suppresses tumor growth in vitro and in vivo. This study identifies FGFR2 as a critical oncogenic driver in EBV and KSHV infections, highlighting its potential as a therapeutic target to inhibit tumor growth and treat associated viral malignancies.